A Data Driven Solution to the Dark MatterProblem - Hoeneisen, Bruce (European Journal of Applied Sciences, 2023)
A data driven solution to the dark matter problem is presented. This short and self-contained overview is intended for a wide audience, with full technical details available in the cited references. We present redundant, independent and consistent measurements of the dark matter particle comoving root-mean-square velocity vhrms(1), or equivalently, of the dark matter temperature-to-mass ratio. These measurements agree with the “no freeze-in and no freeze-out” scenario of spin zero dark matter that decouples early on from the Standard Model sector, e.g., spin zero dark matter coupled to the Higgs boson or to the top quark. 1